Posisi Diri dalam Aktivitas Belajar-Mengajar dan Penyebab Penyimpangan Implementasi Budaya: Perspektif Budaya Bali - Suarsana, I Nyoman (Sunari Penjor : Journal of Anthropology; Vol 2 No 1 (2018)DO - 10.24843/SP.2018.v2.i01.p01, 2018)
Every persons wishing to happy / prosperous live in a hope, any done all his life to run smoothly without a hitch and works well. Based on the full implementation of cultural and / consistently then that happiness can be realized. The pursuit of happiness, in particular can be guided and fully and correctly implement the concept of Luan-Teben, Tri Mandala, and catur guru in various activities, expecsially in learning. Thus philosophy is based on Balinese culture and the Tri Hita Karana Hindu spirit is able to give definite direction toward a happy life for the community of supporters. Dinamik aware of the nature of the implementation of culture change and very often the change is likely to show a discrepancy with a culture that should be inherited. It seems clear that the concept of luan-teben, Tri Mandala, and Catur Guru has not/is not implemented consistently in various activities, especially in teaching and learning activities. Basically these cultural changes caused by the situation and lack of insight into the cultural space for the community of supporters. And thus in a variety of system activity becomes apparent in the culture (the culture of Bali) and therefore often appear/things happen that are not desirable.